ダイ 37 ジ ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク 1996 - 宮本, 仁美; ミヤモト, ヒトミ; 中村, 雅道; ナカムラ, マサミチ; 成田, 修; ナリタ, オサム; 横田, 歩; ヨコタ, アユム; 森永, 裕幸; モリナガ, ヒロユキ; Miyamoto, Hitomi; Nakamura, Masamichi; et al. (1999)
P(論文) この報告は, 第37次南極地域観測隊気象部門が, 1996年2月1日から1997年1月31日まで昭和基地において, 1996年1月23日から1997年1月24日までドームふじ観測拠点において行った気象観測の結果をまとめたものである。観測方法, 測器, 統計等は第36次観測隊とほぼ同様である。越冬期間中に特記される気象現象としては, 次のものがあげられる。1) 昭和基地においては7月から10月にかけて気温が平年より高めに経過し, 特に9月は月平均気温が平年値に比べ6.1℃も高かった。月平均気温は9月と10月に歴代1位の高温を記録した。2) 5月26日から28日にかけて発達した低気圧(ブリザード)に昭和基地が襲われ, 27日には最大風速44.3m/s(歴代3位), 最大瞬間風速61.2m/s(歴代1位)の強風を記録した。3) 昭和基地において, 8年連続で大規模なオゾンホールを観測し, オゾンホールが顕著だった10月, 11月のオゾン全量の月平均値は過去最低を記録した。特に10月の156m atm-cmは, これまで観測された月平均値の中で最小であった。4) 37次では36次に引き続きドームふじ観測拠点において越冬観測を行った。ドームふじ観測拠点における1996年の年平均気温は-54.4℃, 最低気温は5月14日に観測した-79.7℃であった。 This paper describes the results of meteorological observations at Syowa Station from February 1,1996 to January 31,1997,and at Dome Fuji Station from January 23,1996 to January 24,1997 carried out by the Meteorological Observation Team of the 37th Japanese Antarctic Research Expedition (JARE-37). The method of observations, instruments, and statistical methods used by JARE-37 were almost the same as those used by the JARE-36 observation team. Remarkable weather phenomena observed during the period of JARE-37 were the following : 1) From July to October 1996,surface temperature at Syowa Station was higher than the average between 1961 and 1990. Especially, the monthly mean temperature anomaly in September was 6.1℃. Monthly mean temperatures in September and October set the records for the highest temperature in each month. 2) A heavy snowstorm hit Syowa Station from May 26th to 28th. On May 27th, the maximum wind speed was recorded at 44.3m/s (the third highest on record), and the maximum peak gust was recorded at 61.2m/s (the strongest ever). 3) At Syowa Station, the large scale Antarctic ozone hole was observed for the eighth straight year, and the monthly mean total ozone amounts in October and November were recorded as the lowest in observation history. Especially, 156m atm-cm in October was the lowest in the historical record at Syowa Station. 4) During the JARE-37,winter observations were conducted at Dome Fuji Station, the ...